Membangun Narasi Positif Tentang Kesehatan Mental di Media Sosial Instagram - Rizka Aulia Ramadhani; Hani Hadiati Pujawardani (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
This research is motivated by the increasing phenomenon of self-diagnosis and the overflow of unverified information on social media, which has worsened public understanding of psychological issues. In the digital era, mental health has become an increasingly relevant issue, especially among younger generations. Positive narratives play a vital role in restoring meaning, fostering empathy, and addressing the negative stigma associated with mental disorders. This study aims to examine how Kutub.co builds positive narratives about mental health through educational content on social media, analyze audience responses, and identify the challenges faced in the narrative-building process. This research employs a qualitative approach with a descriptive method. The results show that Kutub.co builds positive narratives through visually engaging and communicative content that addresses psychological issues in an accessible and informative manner. Audience responses were generally positive, as reflected in active interactions and support for the messages conveyed. The main challenges faced by Kutub.co include limited human resources and the risk of misinterpretation by the audience. This study indicates that social media can serve as a constructive space to raise public awareness and understanding of mental health issues.